Tingkat Partisipasi Rumah Tangga dalam Pengelolaan Sampah Anorganik di Kawasan Bintaro Jaya Wilayah Kelurahan Pondok Pucung - Diamantha, Insyira Ranti; Zakianis, Zakianis; Hartono, Budi; Ningrum, Yulia Fitria (UI Scholars Hub, 2023)
Background. Community participation in the implementation of waste management can be done at the household level, including sorting out waste and collecting recyclable waste in recycling programs. Bintaro Jaya area has various inorganic waste recycling programs that households can participate in, such as garbage bank programs, garbage dropboxes, and garbage donations to recycling centres or garbage collectors for recycling. The three programs have differences such as the ease of access and the type of waste collected in the program. Aim. The purpose of this study is to analyze the household participation level on inorganic waste recycling programs in Bintaro Jaya area Pondok Pucung urban village region and to find out the factors related. Method. This study used a cross-sectional study design. The analysis unit is a household with a minimum sample based on a two-proportion hypothesis test calculation of 147. Statistical analysis used is chi-square and logistic regression tests. Result. The results of this study indicate that the participation rate of households is 54.5%. The factors related to household participation are the availability of segregated waste bins (p-value < 0.001), and information through socialization (p-value <0.001).